Child Labour in Bangladesh - An Analysis of Gaps and Weaknesses of the Existing Legal Framework - Johannes Norpoth; Lukas Groß; Rahima Aktar (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
Child labour, particularly in its worst forms, harms the health and general welfare of children. It is considered to be a decisive impediment to the development efforts of developing countries. Working children drop out of school early and the resulting comparative lack of knowledge and skills decreases their chances to find well-paid employment in the future. International legal documents, most prominently in the United Nations Convention on the Rights of the Child (UN CRC) and Conventions by the International Labour Organization (ILO), address the problem of child labour and call for an elimination of its worst forms. Despite efforts made at the international and national level child labour remains a common, and often socially accepted, scenario particularly in some developing countries. Bangladesh is one of the countries that still face the challenge of having a large number of children that are working under conditions considered as child labour. The prime reason is poverty. In recent years Bangladesh has taken various measures, including legal measures, to address the situation. This paper reviews reports on the child labour situation in Bangladesh and the current legal framework for child labour and demonstrates that there remain gaps in the legal and policy framework of Bangladesh.
Keywords: 330; Child labour; Bangladesh; Kinderarbeit; Arbeitsrecht; Sozialstandards; Bangladesch